Increasing the Critical Power of Students to Overcome Fake News to Digital Age Through the Science of Hadith Narration - Jundan Jundan; Nurgiyatna Nurgiyatna; Sekar Ayu Aryani (Departement of Mathematics Education, 2022)
The spread of fake news in digital media is very difficult to contain. Fake news has the capacity to wreak havocon society. Fake news has gained ground in the field of had it narration. So that a great deal off ake informationis disseminated as ifit were the truth. Through the science of had ith transmission, the objective is to streng then students' ability to discern fake information in the digital age. This research utilizes a qualitative, descriptive approach. Interview, observation, and document-derived data. The research techniqueutilizes purposive sampling, where as the validity test uset he triangulation method. In conclusion, fake news can berecognized by news content which is in consistent with common reality, is excessively provocative, and makes readers intrigued and concerned. The news is rarely absorbed in accordance with the logic of common sense and content which provokeshatred. The method for preventing fake new sisto; 1). Be wary of topics that defy common sense reasoning, are controversial, and breach convention alguidelines. 2). Identifying fake news producer sand warning others to avoid them. 3) Analyze the conductand personal histories of news anchors, as well as their websites, to obtain additional details about them. 4) Do not quickly spread fake information. 5). Compile a data base of the sources of fake information circulating in the community and track the studies of hoax news observers.